Penguatan Pendidikan Karakter Siswa Melalui Manajemen Bimbingan dan Konseling - Susilo, Dwi Amalia; Nurfaridah, Kharisma; Ginting, Siska Astria Br; Hati, Suci Permata; Nasution, Inom (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Character education plays an important role in shaping one's morals and integrity. However, Indonesia is currently facing a moral crisis marked by an increase in deviant behavior among adolescents. Therefore, strengthening character education has become an urgent need. One of the efforts that can be made is through the management of guidance and counseling in schools. This study aims to examine the concept of character education and the role of guidance and counseling management in strengthening it. The method used is a literature study with qualitative descriptive analysis. The results show that character education is an effort to help students understand, care about, and behave according to ethical values. Good management of guidance and counseling, including planning, organizing, implementing, and evaluating, can contribute to strengthening students' character education. Through systematic and well-planned guidance and counseling management, it is expected to help students develop positive character, improve social skills, and overcome personal problems that can hinder the development of their character.